دراسـة تصنيفيـة لرتبـة جلدية الأجنحة Dermaptera فـي السـاحل السـوري - إحسان, سليمان (Latakia University Journal -Biological Sciences Series, 2019)
تم جمع 131 عينة من مناطق مختلفة من الساحل السوري، خلال الأعوام 1999 ـ 2001 من حشرات رتبة جلدية الأجنحةDermaptera ودرست من الناحيتين المورفولوجية والتصنيفية نظراً لأهميتها في التوازن الحيوي الطبيعي وفي المكافحة الحيوية بوصفها من الحشرات المفترسة في طوري الحورية والحشرة الكاملة لأنواع عديدة من الحشرات. ووضعت مفاتيح تصنيفية للفصائل والأجناس والأنواع بالاعتماد على المعايير المورفولوجية الهامة لها وآلة التسافد الذكرية، تم تعريف ستة أنواع تابعة لأربعة أجناس وأربع فصائل هي: Euborellia annulips ( Luas,1847 ), Labia minor Linneaus, 1857 Labidura riparia ( Palls, 1773 ), Forficula auricularia Linneaus, 1758, Forficula smyrnensis Serville, 1839, pubescens Forficula Gènè,1839 كما تأكد للمرة الأولى في سورية وجود نوعين من الأنواع السابقة وهي: , Labia minor Linneaus, 1857, Labidura riparia ( Palls, 1773 ) Insects belonging to order dermaptera were distributionally and taxonomically studied in the coastal region of Syria. A total of 131 specimens of dermaptera a insect were collected from 1999 to 2001. These insects were chosen for their importance in the natural bio-equilibrium and in the biological control. They are predators of many harmful pests insect in both nymphal and adult stages. The study included sample collection species and genera identification and definition of the most important taxonomic features especially the male external genitalia. Keys for the identification of subfamilies, genera, and species were recorded. A total of six species belonging to four genera and four famillies were recorded, classified and their distribution was defined. The recorded species are: Euborellia annulips (Luas,1847 ), Labia minor Linneaus, 1857, Labidura riparia (Palls, 1773), Forficula auricularia Linneaus, 1758, smyrnensis Forficula Serville, 1839, pubescens Forficula Gènè,1839. Two species are for the first time confirmrd to be recorded in Syria: Labidura riparia ( Palls, 1773), Labia minor ( Linneaus, 1857).